(untitled) (Al-Aasar, 2025)
Special education is a vital discipline that addresses the unique learning needs of exceptional children who differ physically, mentally, or emotionally from their peers. Historically, these children were marginalized, excluded from mainstream education, and considered incapable of learning. However, with the evolution of societies and growing awareness, the importance of educating exceptional children was recognized. The emergence of special schools in Europe during the eighteenth century marked the beginning of structured special education. These schools were later developed worldwide to cater to children with disabilities such as visual, hearing, or intellectual impairments. The primary objectives of special education are to provide social awareness, environmental adjustment, vocational training, personality development, physical and spiritual growth, and solutions to psychological challenges faced by special children. Despite global trends favoring inclusive education, special schools still play an important role, especially for children requiring intensive support. In countries like Pakistan, challenges such as lack of resources, inadequate teacher training, and social stigma hinder the effectiveness of special education. Islam strongly emphasizes the right to education for all, without distinction between normal and special children. Therefore, providing quality education to exceptional children is not only a moral and social responsibility but also a religious obligation. This study highlights the historical development, objectives, challenges, and future prospects of special education while emphasizing the need for inclusive approaches, vocational opportunities, and awareness campaigns to integrate special children into society as productive and respected individuals.